Case Report: Genetic predisposition to low-dose NSAID-induced liver injury in real-world China - Lyu, Yuan; Li, Yangjie; Jiang, Yingying; Li, Qi; Shao, Chen; Fan, Chunlei; Han, Ying; Liu, Hui; Lyu, Lingna; Ding, Huiguo (Frontiers in Medicine, 2025)
Non-steroidal anti-inflammatory drug (NSAID)-induced liver injury represents approximately 10% of reported drug-induced liver injury (DILI) cases, predominantly through idiosyncratic mechanisms. While epidemiological data are largely derived from Western populations with high NSAID utilization, China exhibits lower use of NSAIDs due to cultural preferences and the widespread use of traditional therapies. During the 2022–2023 Omicron outbreak in China, we observed a surge in DILI cases coinciding with increased NSAID use. This study reports two young male patients who developed severe cholestatic DILI following low-dose ibuprofen intake (400 mg), despite lacking conventional risk factors. Genetic analysis revealed compound heterozygous mutations in ABCB11 (encoding the bile salt export pump, BSEP), including the known risk variant p.V444A and the synonymous SNP p.A1028A, with Patient 1 harboring an additional p.A865V mutation. Immunohistochemistry demonstrated abnormal BSEP expression patterns—reduced membrane localization in Patient 2 and intracellular retention in Patient 1—mirroring the pathological features of progressive familial intrahepatic cholestasis type 2 (PFIC-2). These findings suggest that NSAIDs may unmask latent BSEP dysfunction in genetically predisposed individuals, precipitating refractory cholestasis. Our study highlights ABCB11 polymorphisms as critical determinants of NSAID-related DILI susceptibility, even at therapeutic doses. In addition, we propose mechanistic insights into BSEP dysfunction-mediated cholestasis and emphasize pharmacogenetic considerations in NSAID safety assessment across populations.